A next-generation proteome array for Schistosoma mansoni. Issue 7 (June 2016) - de Assis, Rafael Ramiro; Ludolf, Fernanda; Nakajima, Rie; Jasinskas, Al; Oliveira, Guilherme C.; Felgner, Philip L.; Gaze, Soraya T.; Loukas, Alex; LoVerde, Philip T.; Bethony, Jeffrey M.; Correa-Oliveira, Rodrigo; Calzavara-Silva, Carlos E.
Graphical abstract: Highlights: A proteome microarray consisting of 992 Schistosoma mansoni proteins was produced. We describe the methods used to derive the gene list for the array, which represents 10% of the predicted proteome. The array with pilot array using sera from S. mansoni naive individuals and S. mansoni infected individuals was validated. We compare the sera from non-infected individuals with sera from S. mansoni acute and chronically infected individuals. Abstract: A proteome microarray consisting of 992 Schistosoma mansoni proteins was produced and screened with sera to determine antibody signatures indicative of the clinical stages of schistosomiasis and the identification of subunit vaccine candidates. Herein, we describe the methods used to derive the gene list for this array (representing approximately 10% of the predicted S. mansoni proteome). We also probed a pilot version of the microarray with sera from individuals either acutely or chronically infected with S. mansoni from endemic areas in Brazil and sera from individuals resident outside the endemic area (USA) to determine if the array is functional and informative.